Hubungan Pengetahuan Orang Tua Tentang ISPA dengan Upaya Pencegahan ISPA Pada Balita - Nanda Hanastasyia; Iis Aisyah; Emi Lindayani (Jurnal Keperawatan Florence Nightingale, 2024)
The health problem of toddlers related to Acute Respiratory Infections (ARIs) in the working area of Pontang Community Health Center is quite high, reaching 4,000 cases. One of the dominant factors contributing to ARI cases in toddlers is believed to be closely related to the level of parental knowledge in caring for their children. Parents play a crucial role in understanding and implementing appropriate health measures, thereby minimizing the occurrence of ARIs in toddlers. The objective of this study is to determine the relationship between parental knowledge of ARIs and ARI prevention efforts in toddlers in the Pontang Community Health Center area. This is a quantitative correlation study with a Cross-Sectional approach, with a sample size of 98 respondents. Sampling technique used is proportional random sampling method. The results of the Spearman-Rank statistical test yielded a p-value of 0.001, indicating a significant relationship between parental knowledge of ARIs and ARI prevention efforts in toddlers. The better the parents' knowledge of ARIs, the more effective they are in monitoring their toddlers' daily activities, thereby reducing the risk of ARIs as parents can better anticipate potential health issues. Thus, it is hoped that parents of toddlers in the Pontang Community Health Center area can enhance their understanding of the importance of implementing ARI prevention measures to safeguard their children from the risk of ARIs.